MODERN DIAGNOSTICS OF TUBERCULOUS SPONDYLITIS - Alimova G. S. (Web of Journals Publishing, 2025)
Tuberculous spondylitis, also known as hospital-acquired tuberculosis, is a rare but serious manifestation of tuberculosis infection affecting the spine and spinal cord. This article reviews the epidemiology, pathophysiology, clinical presentation, diagnosis, and treatment options for tuberculous spondylitis.
Keywords: Tuberculous spondylitis, pathophysiology, modern diagnosis.